2019
DOI: 10.1186/s12979-019-0168-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of plasma high-sensitivity C-reactive protein concentrations with all-cause and cause-specific mortality among middle-aged and elderly individuals

Abstract: BackgroundThe association of high-sensitivity C-reactive protein (hsCRP) with mortality is controversial. We aimed to investigate the associations of hsCRP concentrations with the risks of all-cause and cause-specific mortality and identify potential modifying factors affecting these associations among middle-aged and elderly individuals.MethodsThis community-based prospective cohort study included 14,220 participants aged 50+ years (mean age: 64.9 years) from the Health and Retirement Study. Cox proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…It is also important to note that sex was not a modifier in our study. Some studies showed a positive association in both sexes ( 9 , 24 , 27 ), while significant differences appeared to exist in a single sex [mostly men ( 29 , 42 , 43 )]. However, whether men or women were at a greater risk remains controversial ( 9 , 24 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that sex was not a modifier in our study. Some studies showed a positive association in both sexes ( 9 , 24 , 27 ), while significant differences appeared to exist in a single sex [mostly men ( 29 , 42 , 43 )]. However, whether men or women were at a greater risk remains controversial ( 9 , 24 , 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…CRP has been commonly assayed for infections (11), in-hospital complications (12), prognosis influences (13), and aging-related health outcomes in clinical applications, especially cardiovascular and metabolic disease risk (14,15). Higher hsCRP levels have been proposed as a predictor of all-cause mortality in many (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) but not all studies (29). Inconsistent results may exist due to sex, ethnic or age differences in the populations, and the strength of the association also varied across studies, from 1.14 to 3.64 (hazard ratios or relative risks).…”
mentioning
confidence: 99%
“…CRP is correlated with a high mortality risk factor. Some studies associate CRP with several elderly diseases, including MS, diabetes or obesity, but also with cancer and cardiovascular risk 14 . In the group with diet therapy, a statistically significant reduction of CRP was obtained, which implies that diet therapy is an effective monotherapy alternative.…”
Section: Discussionmentioning
confidence: 99%
“…With aging, loss of homeostasis alters the production of cytokines, leading to a low-grade chronic systemic pro-inflammatory state characterized by permanently elevated levels of IL-6 and CRP. This state, also called "inflammaging" [9], is considered to be a promotor of accelerated aging [10], age-related syndromes such as frailty [11][12][13][14], and mortality [15][16][17][18] in older adults. Thus, capturing iron status among older adults may be relevant to the promotion of healthy aging and the prevention of age-related chronic diseases.…”
Section: Introductionmentioning
confidence: 99%